2011
DOI: 10.1111/j.1399-6576.2011.02525.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the implementation of WHOSurgical Checklist in Finland: improvements in activities and communication

Abstract: The checklist increased OR teams' awareness of patient-related issues, the procedure and expected risks. It also enhanced team communication and prevented communication failures. Our findings support use of the WHO checklist in various surgical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 28 publications
4
83
0
9
Order By: Relevance
“…5,[18][19][20][21][22][23] Specifically, use of the WHO SSC has shown a decrease in inpatient morbidity and mortality 2,[4][5][6][7]24 as well as improvement in teamwork skills, communication, and adherence to process measures. 1,23,[25][26][27] Nevertheless, Ko et al's recent systematic review of checklist use in medicine has shown limited evidence of their effectiveness. 28 Analysis of the studies indicated that many were of poor quality with low levels of evidence and a high rate of bias.…”
Section: Discussionmentioning
confidence: 99%
“…5,[18][19][20][21][22][23] Specifically, use of the WHO SSC has shown a decrease in inpatient morbidity and mortality 2,[4][5][6][7]24 as well as improvement in teamwork skills, communication, and adherence to process measures. 1,23,[25][26][27] Nevertheless, Ko et al's recent systematic review of checklist use in medicine has shown limited evidence of their effectiveness. 28 Analysis of the studies indicated that many were of poor quality with low levels of evidence and a high rate of bias.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Another study, showing improvement of patient identification and surgical site confirmation, emphasised that better understanding of each team member's role aided in better communication and teamwork. [8] Other studies have shown contradictory results. Urbach et al [9] investigated the effect of surgical safety checklists at 101 hospitals.…”
Section: Researchmentioning
confidence: 99%
“…Studies used 2 main methodologies to assess team member attitudes: focused interview of a random sample of operating theatre staff (2 studies) 32,33 and a surgical team questionnaire pre-and post-SSC intervention (8 studies). 9,[34][35][36][37][38][39][40] The studies varied in participant size with 37 to 40 participants in focus group studies across the OR disciplines, 32,33 while the surgical team survey questionnaire studies had participant sizes as large as 1748. The surgical questionnaires were based on resources from previous studies or adapted from the surgical attitudes questionnaire (SAQ).…”
Section: Staff Perceptionmentioning
confidence: 99%
“…36 Additionally, of the 5 studies that examined this category, participants in 3 studies suggested that SSC did not substantially improve team member identification. 9,32,35,39 Six studies conducted crosssectional analyses across OR staff disciplines (surgeons, anesthetists, and nurses). 34,35,37,39,40,42 Nurses valued the gains made by SSC introduction far more than other staff members, but also were the most sensitive to the barriers inhibiting its completion, such as poor teamwork.…”
Section: Staff Perceptionmentioning
confidence: 99%
See 1 more Smart Citation